“Non ha tan buena escuela cuemo casa de señores”. El consejero caballeresco en el Libro del cavallero et del escudero de don Juan Manuel - Cossío Olavide, Mario (2019)
In this article I analyze the figure of the counselor in Juan Manuel’s first work, the Libro del cavallero et del escudero. To this end, I establish the relationship between the text, an early product of the author’s larger literary and political project, and the literary production of the courtly and aristocratic clerecía that was promoted as the basis of new courtly models starting in the reign of Alfonso X. My analysis centers on the characteristics that converted the counselor into a transmitter of a chivalric encyclopedism which unified the knowledge of the lettered scholars and the practical know-how of defensores. I propose that this counselor figure can be interpreted as a discursive mechanism created to support a new project of lordly legitimacy: the seigneurial clerisy.